2016
DOI: 10.1590/1808-1657001032014
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological characterization of leptospirosis in horses in the state of Pernambuco, northeastern Brazil

Abstract: An epidemiological survey aiming to determine the occurrence of anti-Leptospira antibodies and to identify risk factors was carried out in horses of the Pajeú microregion, state of Pernambuco. Sera from 100 horses from 38 properties in four counties in the region were examined by the microscopic agglutination test (MAT), using 24 Leptospira spp. serovars as antigens. Of the 100 samples tested, 28 (28%) were positive. Most prevalent serovars were Patoc (35.71%), Butembo (32.14%) and Sentot (14.30%). Supply of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 12 publications
2
9
1
4
Order By: Relevance
“…The analyzed variables did not show association with leptospiral infection. This disagrees with the work by Alves et al (2016) in Pernambuco, where pasture, the main food source, was considered a risk factor, stemming from the fact that natural reservoirs of the disease may be excreting the agent into the environment. Fodder, which is the main food source for animals in this region, originates from swampy areas, which does not cause great concern since in the region of the current study, the soil is sandy and Semina: Ciências Agrárias, Londrina, v. 40, n. 2, p. 701-712, mar./abr.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…The analyzed variables did not show association with leptospiral infection. This disagrees with the work by Alves et al (2016) in Pernambuco, where pasture, the main food source, was considered a risk factor, stemming from the fact that natural reservoirs of the disease may be excreting the agent into the environment. Fodder, which is the main food source for animals in this region, originates from swampy areas, which does not cause great concern since in the region of the current study, the soil is sandy and Semina: Ciências Agrárias, Londrina, v. 40, n. 2, p. 701-712, mar./abr.…”
Section: Discussioncontrasting
confidence: 95%
“…In the present work, MAT revealed that 57.69% of animals were reactive against leptospirosis. Similar results were described by in the states of Mato Grosso do Sul (MS), Mato Grosso (MT), Ceará (CE), Pernambuco (PE), and Bahia (BA) and by Pinna et al (2008) in Rio de Janeiro (RJ), where they detected 52.63% and 55.40% of MAT seroreactive animals, respectively; lower results (28%) were detected by Alves et al (2016) in Pajeú (PE) using the same test. These serological results may have been influenced by the differences in the prevalence of animal leptospirosis in their respective locations, in addition to being a reflection of the study periods, which may have enhanced or decreased the probabilities of infection occurring in these equines.…”
Section: Discussionsupporting
confidence: 84%
“…Taking into account the significant level of occurrence of the Icterohaemorrhagiae incidental serogroup, it is important to analyze how the animals come into contact with rodents and how to proceed with the implementation of rodent control (Verma et al, 2013), adequate sealing of waste and waste depot sites, as well as periodic cleaning of feeders and drinkers used by the animals (Alves et al, 2016). However, for infections of the Australis serogroup, control becomes more complex, since the main form of transmission is intraspecies infection (Ellis, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, five 2‐fold dilutions of serum samples from 1:25 to 1:4,000 were used. Samples were tested for 16 serovars: Leptospira interrogans serovar Australis (Australis), Leptospira interrogans serovar Autumnalis (Autumnalis), Leptospira interrogans serovar Sejroe (Sejroe), Leptospira interrogans serovar Canicola (Canicola), Leptospira interrogans serovar Ballum (Ballum), Leptospira interrogans serovar Celledoni (Celledoni), Leptospira interrogans serovar Copenhageni (Copenhageni), Leptospira borgpetersenii Javanica (Javanica), Leptospira interrogans serovar Grippotyphosa (Grippotyphosa), Leptospira interrogans serovar Hardjo (Hardjo), Leptospira interrogans serovar Hebdomadis (Hebdomadis), Leptospira interrogans serovar Icterohaemorrhagiae (Icterohaemorrhagiae), Leptospira interrogans serovar Pomona (Pomona), Leptospira interrogans serovar Pyrogenes (Pyrogenes), Leptospira interrogans serovar Tarassovi (Tarassovi) and Leptospira interrogans serovar Wolffi (Wolffi) (Adler, ; Alves et al, ; Dreyfus et al, ; Filho et al, ). The antigens were stored at 28°C from 5 to 10 days in EMJH (Ellinghausen & MCcullough, ) culture (Difco ® , USA) that was enriched with bovine albumin fraction V (Inlab ® , Brazil) (Ellinghausen & McCullough, ).…”
Section: Methodsmentioning
confidence: 99%